Will environmental land management fill the income gap on upland-hill farms in England? - Holt, Alison; Morris, Joe (Elsevier, 2022)
The decision by the UK Government to withdraw from the European Union has prompted a major review of Agricultural and Environmental Policy. Focussing on upland farms in England, we explored the implications of switching from direct income support to ‘public money for public goods’. We posed two questions: (i) what public goods can upland farms provide? and (ii) can the rewards for environmental land management options fill the income gap due to loss of income support? Working with three volunteer upland farms, we combined the methods of a map-based natural capital and ecosystem services assessment with those of financial farm business appraisal. From this we produced a synthetic ‘Pen Farm’ Case to demonstrate the methods, produce indicative results and help support decisions by policy makers and practitioners during policy transition. We conclude that plugging the income gap could require a threefold increase in net income from environmental options. This will, however, require resetting the relationship between agricultural and environmental outcomes, particularly involving changes to livestock and grassland management. Furthermore, as environmental services become a core business function, payments by results must provide sufficient return on effort and assets to maintain the viability of the upland farm business. We also conclude that the integration of natural capital and farm business accounting is critical to support decision making at the farm and landscape scales as the transition to environmental land management is implemented.
Keywords: Environmental land management; Agriculture; Uplands, farm business; Natural capital; Policy